Mapping Ecosystem Services in Colombia: Analysis of Synergies, Trade-Offs and Bundles in Environmental Management - Burgos-Ayala, A (Elsevier B.V., 2024)
Ecosystem services (ES) have gained significant attention in recent years from the global environmental initiatives that involve science and policy. Multiple scholars have analyzed how ES are integrated with environmental policies, plans, and strategic assessments. However, there is a lack of information on how countries translate these policies, plans and assessments into concrete environmental management actions that integrate an explicit ES approach. To help fill this gap, we analyze how the Colombian Regional Autonomous Corporations (CARs) have used the ES approach in their environmental management projects implemented between 2004 and 2015. This study aims to analyze the type and diversity of ES managed by the CARs, as well as the synergies, trade-offs, and bundles of ES prioritized by them. We used content analysis of the CARs reports and statistical analysis to explore whether CARs explicitly use the ES concept. Our results showed that provisioning, regulating, and cultural ES were similarly prioritized by the CARs, however, explicit mention of ES was limited. Regulating services showed remarkable potential for synergies, and there was a pattern of trade-offs between cultural and some regulating and provisioning services. We found three bundles of ES: “Restoration and conservation of agrosystems”, “Mosaic of services” and “Farming and fibers” occupying, respectively, 9, 36 and 55% of the total area of Colombia. Our findings show that multiple ES are targeted and affected by environmental management actions. The contribution of this study has the potential to inform adequately policy decisions to be used in environmental management and planning practices to prioritize areas for maximizing ES provision. © 2024